Age influences magnitude but not duration of response to levodopa. Issue 1 (January 1993) - Durso, R; Isaac, K; Perry, L; Saint-Hilaire, M; Feldman, R G
Abstract : Following an all-night fast, 45 patients with Parkinson's disease were examined using certain motor items present in the United Parkinson's Disease Rating Scale. All were given a single tablet of carbidopa 25 mg and levodopa 250 mg and re-examined 90 minutes later. In addition to this evaluation, 23 of these patients underwent further scoring over a 4-hour period. A significant negative correlation was found between age and one important aspect of drug-derived benefit: magnitude of response. In contrast, age had no apparent influence on duration of benefit from the drug. Although baseline (fasting) scores were predictably correlated with duration of disease, magnitude of response was not adversely influenced by this variable. Not all Parkinsonian signs were equally influenced by age. Whereas the poor response of gait and bradykinesia appeared to be dependent on age, no such effect was noted on rest tremor scores. The data indicate that in patients with Parkinson's disease treated long term, factors associated with age rather than duration of disease may have a stronger adverse influence on magnitude of response to levodopa.